INTERNATIONAL RECOGNITION AS A STRATEGY FOR ENHANCING THE GLOBAL COMPETITIVENESS OF LOCAL HAND-DRAWN BATIK - Vita Fajariani, Sukma; Utama, Mahendra Pudji (International Journal of Cultural and Social Science, 2026)
This study examined the forms of international recognition within the Wukirsari hand-drawn batik ecosystem. The research identified multiple avenues through which artisans and small-scale producers gained global acknowledgment, including participation in international exhibitions, cooperation with foreign buyers for small-scale exports, coverage by foreign media and digital platforms, and recognition as intangible cultural heritage. Data were collected through qualitative observation and interviews with local batik stakeholders and analyzed using a theory-driven framework that linked recognition practices to social, economic, and cultural dimensions. The findings revealed that international exhibitions enhanced visibility and legitimacy, export cooperation strengthened economic resilience and network ties, media coverage amplified symbolic prestige, and heritage recognition preserved cultural identity while providing global validation. The study concluded that these interconnected forms of recognition collectively contributed to both the sustainability of local craftsmanship and the global positioning of Wukirsari batik. The results provide insights for policymakers, cultural institutions, and small-scale artisans seeking to strategically leverage international platforms for cultural and economic advancement.